PENGARUH AUDIT TENURE, REPUTASI AUDITOR, SPESIALISASI AUDIT, DAN UKURAN PERUSAHAAN TERHADAP KUALITAS AUDIT PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Yolanda Siregar; Duma Megaria Elissabeth (JURNAL ILMIAH SIMANTEK, 2018)
This research aims to identify and analyze whether Audit Tenure, Auditor Reputation, Audit Specialization, and Client Size to Audit Quality. The population of this research is banking company listed on Indonesian Stock Exchange. The method of this research is a descriptive statistical analysis and logistic regression analysis. Independent variables in this study is Audit Tenure, Auditor Reputation, Audit Specialization, and Client Size, while the dependent variables is Audit Quality. Total population of this research are 41 companies using purposive sampling obtained 26 companies from 2012 to 2016. The type data used to secondary data. The result of this research showed that Audit Tenure and Auditor Reputation, Audit Specialization, and Client Size had significant effect on Audit Quality. In partial, Audit Tenure and Reputation Auditor had significant effect to Audit Quality,while Audit Specialization and Client Size not significant to Audit Quality.